prime minister decree No. 1730/2017 on applying the tariff of drinking water, sewage and charges for service sustainability = قرار رئيس مجلس الوزراء رقم 1730 لسنة 2017 بشأن تطبيق تعريفة مياة الشرب والصرف الصحي وقيمة مقابل استدامة الخدمة / Prime Minister. - Egypt. Prime Minister. (2025)
Decree of the prime minister no. 1730 of the year 2017 – table no. (1) tariff of drinking water and sewage -- table no. (2) segments and activities of the customers قرار رئيس مجلس الوزراء رقم 1730 لسنة 2017 – جدول رقم (1) تعريفة مياه الشرب والصرف الصحى – جدول (2) شرائح وأنشطة العملاء